Fishery and population dynamics of the obtuse barracuda Sphyraena obtusata (Cuvier) landed by trawlers at Cochin, south-west coast of India - Najmudeen, T M; Seetha, P K; Zacharia, P U (Indian Journal of Fisheries, 2015)
Fishery and population characteristics of the obtuse barracuda Sphyraena obtusata (Cuvier) landed by mechanised trawlers off Cochin were studied for the period 2010-2012. The average annual landings of barracuda was 184 t of which S. obtusata formed 65%. Seasonal peak in catch and catch rate was recorded during August, followed by February and May. The von Bertalanffy growth parameters (VBGF) estimated using ELEFAN were Lâˆž = 34.2 cm, K = 0.71 year-1 and t0 = -0.0000000025. The lengths attained at the end of 1, 2, 3, 4 and 5 years were 17.4, 25.9, 30.1, 32.2 and 33.2 cm, respectively. Recruitment was almost round the year with a major peak during February-May and a minor peak during July, together accounting 80% of the total recruitment. Natural mortality (M), fishing mortality (F) and total mortality (Z) were 1.35, 1.54 and 2.89 respectively. The length at first capture was 23.5 cm (age 1.64 years). The optimum length for exploitation (Lopt) was 20.9 cm at the age of (topt) of 1.3 years. Mean size in the catch (25.1 cm) was higher than Lopt. The resource is being exploited at a level marginally higher than E50 (E = 0.53), indicating optimal exploitation. Though the annual average yield is only marginally (6%) higher than the MSY estimated, there is no need for reducing the fishing effort from the prevailing rate. Instead, as the yield and biomass per recruit and yield and biomass curves showed that the maximum yield and yield per recruit could be obtained by increasing the present level of fishing, marginal increase in the effort is prescribed to sustain the fishery.